Chest discomfort at night and risk of acute coronary syndrome: cross-sectional study of telephone conversations - Wouters, Loes T (Fam Pract, 2020)
BACKGROUND: During telephone triage, it is difficult to assign adequate urgency to patients with chest discomfort. Considering the time of calling could be helpful. OBJECTIVE: To assess the risk of acute coronary syndrome (ACS) in certain time periods and whether sex influences this risk. METHODS: Cross-sectional study of 1655 recordings of telephone conversations of patients who called the out-of-hours services primary care (OHS-PC) for chest discomfort. Call time, patient characteristics, symptoms, medical history and urgency allocation of the triage conversations were collected. The final diagnosis of each call was retrieved at the patient’s general practice. Absolute numbers of patients with and without ACS were plotted and risks per hour were calculated. The risk ratio of ACS at night (0 to 9 am) was calculated by comparing to the risk at other hours and was adjusted for gender and age. RESULTS: The mean age of callers was 58.9 (standard deviation ±19.5) years, 55.5% were women and, in total, 199 (12.0%) had an ACS. The crude risk ratio for an ACS at night was 1.80 (confidence interval 1.39–2.34, P < 0.001): 2.33 (1.68–3.22, P < 0.001) for men and 1.29 (0.83–1.99, P = 0.256) for women. The adjusted risk ratio for ACS of all people at night was 1.82 (1.07–3.10, P = 0.039). CONCLUSIONS: Patients calling the OHS-PC for chest discomfort between 0 and 9 am have almost twice a higher risk of ACS than those calling other hours, a phenomenon more evident in men than in women. At night, dispatching ambulances more ‘straightaway’ could be considered for these patients with chest discomfort. TRIAL NUMBER: NTR7331.